SOIL NUTRIENT STATUS UNDER ACACIA SENEGAL WILD PLANTATION IN THE SAHEL ZONE OF JIGAWA STATE, NIGERIA (2013)
Soils in sahel zone of Jigawa state have been reported to have poor fertility status due to soil erosion and desertification. Acacia senegal is generally planted in plantations in the state for the production of Gum Arabic and control of soil erosion. However, documentation of the potential of Acacia senegal to improve soil nutrient under plantation is scanty. Nutrient status under Acacia senegal plantation in sahel zone of Jigawa state was therefore investigated. Four 30 x 30m plots were randomly chosen within the plantation with adjacent open woodland of the same size used as control in a randomized complete block design. Decomposition and mineralisation of monthly litterfall collected from each plot for six months were measured using litterbag technique. Litter fractions were collected, oven- dried and analysed for Nitrogen (N), Phosphorous (P), Potassium (K), Calcium (Ca) and Magnesium (Mg) using standard procedures. Measurement of Diameter at Breast Height (DBH) and height of two mean trees per plot were taken. Representative trees were sampled for biomass estimation. Fresh samples of tree foliage, branch, stem and root were weighed and analysed for macro- and micro-nutrients. Soil samples were taken from 0-15, 15-30 and 30-60cm depths in a Randomized Complete Block Design (RCBD) and analysed for micro- and macro- nutrients. Soil acidity was determined in water and 0.01M CaCl2 solution using a soil solution ratio of 1:2.5. Data were analysed using descriptive statistics, linear correlation and ANOVA at p = 0.05. Total litterfall was 3.1 kg/ha/yr and litter decomposition rate was faster in early stages of decomposition with 43.6% mass loss. Mean macro-nutrients concentrations for the decomposed litter were: P (0.16 ±0.22 mg/kg); K (0.32 ±0.28 cmol/kg); Ca (3.1 ±1.2 cmol/kg); Mg (0.49 ±0.16 cmol/kg) but highest at soil depth 0-15cm: P (34.1 ±11.5 mg/kg); K (0.32 ±0.12 cmol/kg); Ca (6.5 ±1.8 cmol/kg) and Mg (3.3 ±0.76 cmol/kg). Basal area of the plantation was 22.0 m2/ha, while tree biomass was 1,232.9 kg/ha. Tree micro-nutrients concentration had significant relationship with tree components but not with diameter class. Nitrogen (3.5cmol/g) and copper (0.02 mg/kg) concentrations were higher in foliage with calcium in root (2.6 cmol/g). The concentrations of macro- nutrients in soil: N (0.09-0.03 cmol/g); Ca (3.8-2.4 cmol/g) and K (0.18-0.09 cmol/g) decreased as soil depth increased except for magnesium (0.28-0.72 cmol/g) and sodium (0.11-0.15 cmol/g). Soil macro-nutrients concentration were higher in plantation: N (0.25 cmol/g); K (0.14 cmol/g); Ca (3.9 cmol/g) and Mg (0.66 cmol/g) than in open woodland: N (0.03 cmol/g); K (0.12 cmol/kg); Ca (2.9 cmol/kg) and Mg (0.35 cmol/kg). Positive correlation was observed between soil depth and clay (r= 0.64) as well as between silt and calcium (r= 0.74). Soil acidity in CaCl2 solution ranged from 4.2 to 5.6 and from 4.7 to 5.9 in water. Soil nutrients were higher in the plantation than in the open woodland as a result of litter decomposition and mineralisation. This implied enhanced soil nutrient status under Acacia Senegal plantation in the study area.